PATERSON E ZDERAD'S THEORY: HUMANISTIC APPLICABILITY IN NORMAL BIRTH - Nayara Rubia Coelho; Lilian Maureira Vergara (Universidade Federal do Paraná, 2015)
The humanization process in normal birth promotes the "art of humanized care" and the applicability of the humanistic theory constitutes a theoretical framework that supports the existential exchange and dialogical relation between nurse and parturient. The objective in this study was to describe and reflect on the contribution to the humanized theoretical-practical relationship in normal birth in the light of the humanistic theory. An exploratory and descriptive bibliographic review was undertaken of on-line articles taken from the databases: Latino-Americana e do Caribe em Ciências da Saúde, Base de Dados de Enfermagem and Scientific Electronic Library Online, published between 2002 and 2014. The results evidenced that the humanistic theory strengthens the professional's identity, autonomy, need to reflect on humanized care, rescue the experience of being-with-the-other, in a dialogical encounter. Thus, the process based on the relation between the experienced and dialogued encounter contributes to effective and safe care.